(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Objective of study: To evaluate the impact on thrombotic events, major bleeding, and all-cause mortality of self-monitoring or self-treatment with oral anticoagulants compared with standard monitoring. Methodology: For this review update, we re-ran the searches of the PubMed, Science Direct and google Scholar from 2000 to 2021. We checked bibliographies and referred the work of authors of relevant studies. We did not apply any language restrictions. Discussion: Self-monitoring of anti-coagulation as its limited only to the patients who are capable of performing the required techniques and can bear the cost as well. Conclusion: Thromboembolic events were reduced with self monitored anti coagulant treatment.